Expanding Europe through Memory: The Shifting Content of the Ever-Salient Past. (January 2015) - Verovšek, Peter J.
Collective memories of war and suffering have been crucial to the development of European integration since 1945. My basic thesis is that remembrance has also played an important role in the accession of new states to the organization that has come to be known as the European Union (EU). As the EU has expanded into new regions of Europe, particularly the post-dictatorial south and the post-communist east, continental institutions and existing member-states have been confronted by conflicting understandings of the past. Although the past has continued to push states towards membership in the EU, the nature of these remembered experiences has changed through the various rounds of expansion. In addition to tracing the role that memory has played in the widening of Europe, I argue that these confrontations have sparked important debates about the meaning of the past for Europe today.